Impact of TAM on Generation Z User Intention towards TikTok Live Shopping - Anggalia Wibasuri; Ni Kadek Dwi Ayundari; M. Afsori; Dwiga Agus Nugroho (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Purpose: The development of digital technology has transformed the marketing landscape into social commerce, exemplified by TikTok Shop's Live Shopping feature. However, the acceptance level of this technology among Gen Z as digital natives requires in-depth analysis. Therefore, this study aims to analyze the influence of Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) on Behavioral Intention (BI) with Attitude Toward Using (Yufi, Fadli, & Khalida) as a mediating variable based on the Technology Acceptance Model (Iswarani & Gautama). Research Methodology: The study employed an associative quantitative method. Data were collected via online questionnaires from 100 respondents selected using probability sampling. Path analysis was performed using IBM SPSS version 25 software. Results: The findings indicate that Perceived Ease of Use significantly affects ATU, whereas PU does not directly influence Attitude. Furthermore, ATU significantly influences Behavioral Intention. Conclusions: It is concluded that Attitude acts as a full mediator. This implies that for Generation Z, forming a positive attitude is a mandatory prerequisite that bridges the gap between technology perception and the actual intention to use. Limitations: This research focused on a single creator (@williesalim) and Generation Z; therefore, generalizations to other demographics should be made with caution. Contributions: This research provides a theoretical contribution by explicitly demonstrating the full mediating role of user attitude between technical platform perceptions and behavioral intention in a live shopping ecosystem, thereby extending TAM literature in the context of digital natives.